Desain Dan Perancangan Mesin Pengering Padi Dengan Pemanas Gas Elpiji Sistem Terpadu - Supriyono Supriyono; Leo Aji Saputro (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Technological development is urgently needed to handle rice drying, namely by designing and designing rice drying machines, by utilizing heating from burning LPG gas which is arranged in an integrated system. The purpose of this paper is to design and design a rice drying machine, selecting machine components and including analysis of the strength of the dryer shaft by knowing von Misses stress, displacement and safety factors. The design of the rice drying machine uses 1 source of electric motor driving power to operate an integrated drying and heating system. With the power of 0.5 HP (0.37 kW) it is planned to be able to dry rice with a capacity of 30 kg/hour. The power generated by the electric motor is used to move pulley-1 (drive), which is transmitted using V-belt transmission to move pulley-2 (gear box and dryer blower). The length of the first belt transmission (L) is 813 mm and the second is 1270 mm. And uses a chain transmission with type number 40 which has a distance of 12.70 mm with a chain length of 76 links. The bearing used is a radial ball bearing with a single row UCP 205. Based on the results of the analysis of the rice drying machine shaft using solidwork software, Von Misses stress value is 40.55 MPa, displacement value is 0.19 mm, and safety factor value is 13.07, so from the simulation results this rice drying shaft can be said to be safe in accepting workloads